Anti-fungal efficacy of aqueous leaf extracts Neem (Azadirachta indica) in the treatment of tap water - Habberrih, Salah Omar Abdulali; Islam, Mir Sujaul; Zaied, Khalid; Che Ku Mohammad, Faizal; Fadzil, Mat Yahaya (EM International., 2022)
High-quality drinking water coming from treatment plants is susceptible to pollution and severe deterioration due to the drinking water delivery system prior to access to consumers’ faucets. The results of this study confirmed that Neem leaves extract and chlorine at all concentrations had antifungal activity during tap water treatment. This study has provided excellence about the ability of Neem leaves extraction and chlorine as a disinfectant for Rhodotorula mucilaginosa and Aspergillus spp. in treating tap water. The most notable factors were the dosage, time, and agitation selected to evaluate their effects on reducing the development of fungal communities in drinking water using the central composite design (CCD) in the response surface methodology (RSM). The CCD was performed with a 2 complete central composite design with five different stage coordinate components. Because the Neem leaves can be processed locally and should also be encouraged for use in water treatment. This will eventually reduce the high costs and health risks associated with chemical water treatment. This technology is cheap, conventional, readily available, and suitable for rural areas, as nature’s biological methods generate no treatable waste.